The Application of Direct and Indirect Methods in Teaching “Telling Time” Through Microteaching Practice at MTs Al-Amiriyyah (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to analyze the effectiveness of the application of direct and indirect methods in teaching English, specifically the topic of "Telling Time," at MTs Al-Amiriyyah through microteaching practice. This research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research subjects consist of an English teacher and the students of class VIII A. The data were thematically analyzed to identify significant patterns in the teaching process. The findings indicate that the direct method is effective in building students' foundational understanding of time concepts, as it emphasizes explicit and concrete use of the target language and allows teachers to easily assess students' comprehension through drilling. On the other hand, the indirect method proved to enhance students’ ability to use English more naturally through contextual activities such as role play and daily schedule games. Moreover, students with kinesthetic learning styles responded more positively to the indirect method, as it enables them to learn through physical activity and direct participation. These findings suggest that a combination of both methods yields optimal results: the direct method is effective for the initial stage of concept acquisition, while the indirect method supports the development of communicative skills in a functional and enjoyable manner, aligning with students' characteristics.